Improved adhesive strength and toughness of polyvinyl acetate glue on addition of small quantities of graphene - COLEMAN, JONATHAN; KHAN, UMAR; MAY, PETER (My University, 2013)
We have prepared composites of polyvinyl acetate (PVAc) reinforced with solution exfoliated graphene. We observe a 50% increase in stiffness and a 100% increase in tensile strength on addition of 0.1vol% graphene compared to the pristine polymer. As PVAc is commonly used commercially as a glue, we have tested such composites as adhesives. The adhesive strength and toughness of the composites were up to 4 and 7 times higher, respectively, than the pristine polymer.
PUBLISHED
We acknowledge financial support from Science Foundation Ireland through the Principle Investigator scheme (grant number 07/IN.7/I1772
Keywords: polyvinyl acetate; Nanoscience & Materials